Group Decision Support System Untuk Menentukan Manajer Proyek Pada Perusahaan Smart Integrated System Menerapkan Metode Fuzzy Tahani - Arif Athallah; Diana Diana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Project is a series of activities carried out within a limited period of time with certain resources to achieve the best results in the future. In a series of activities, the project must have problems or obstacles. The success of the project is influenced by who and how to deal with problems or obstacles during the project. The project manager is the person chosen to be responsible for activities in the project management process for the benefit of the company and is a core figure in the success of a project and is the most influential factor in the success of project management. The obstacle that exists in Smart Integrated System companies is that there is no project manager selection process that implements a requirement to become a project manager. Plus, the role of the project manager is always changing and being chosen on the spur of the moment and randomly. This study aims to overcome problems that may arise in group decision making in Smart Integrated System companies. Solving problems in Smart Integrated System (SIS) company will use a system called a website-based Group Decision Support System (GDSS) that will apply the Fuzzy Tahani method. Admin determines the high Query Fuzzification value for each set of Membership Function criteria / sub-criteria. The results of system testing on four project manager candidates found that a candidate named Jaka has the right to become a project manager. The project manager candidate selected according to the system is the best project manager candidate based on the criteria provided.